Phytochemicals from Cactaceae family for cancer prevention and therapy - Orozco-Barocio, Arturo; Sánchez-Sánchez, Marina A.; Rojas-Mayorquín, Argelia E.; Godínez-Rubí, Marisol; Reyes-Mata, María Paulina; Ortuño-Sahagún, Daniel (Frontiers in Pharmacology, 2024)
Cancer is a global health issue, increasingly prevalent and a leading cause of mortality. Despite extensive research, conventional treatments remain aggressive, often damaging healthy cells, and exhibit limited efficacy. Addressing drug resistance and enhancing treatment effectiveness are critical challenges in advancing cancer therapy. This review examines the potential of natural plant compounds, particularly phytochemicals and their derivatives, in developing novel anticancer agents. These metabolites have a long history in traditional medicine, with 42% of molecules approved for cancer treatment between 1981 and 2019 being either natural products or derivatives. The Cactaceae family, which comprises more than 1500 species, represents a largely untapped source of potentially useful chemopreventive and anticancer agents. Although more than 3000 plants and their derivatives have contributed to chemotherapeutic development, cactus species have received limited attention until recently. Emerging evidence highlights the anticancer potential of fruits, stems, and cladodes from various cactus species. This review provides a comprehensive and current overview of experimental studies on Cactaceae in cancer research, aiming to pave the way for the development of innovative, natural cancer therapeutics and contribute to the ongoing battle against this formidable disease.